Kualitas Pelayanan Kesehatan di Puskesmas Padongko - A. Pananrangi.M; Andi Tenri Nippi; Rahmat Panyyiwi; Suprapto Suprapto (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background; Increasing public awareness of their rights to obtain services, including health services, is a positive indicator of increasing awareness of the importance of health. This study aims to determine the quality of health services at Puskesmas Padongko, Barru District, Barru Regency. Methods: This research type used is descriptive qualitative. The data used are primary data and secondary data. Primary data as informants are Puskesmas Padongko staff, patients, and community leaders. Meanwhile, secondary data is carried out through literature searches, journals, and other scientific works. Data collection techniques are interviews, observation, and documentation. Then the data analysis techniques, namely; data reduction, data presentation, and drawing conclusions. The results showed that although there was still a lack of facilities and facilities, in general, it could be concluded that Puskesmas Padongko had shown a fairly good quality of health services. Conclusion: Although there is still a lack of facilities and infrastructure, in general, it can be concluded that Puskesmas Padongko has shown a fairly good quality of health services.